Power Relations In The Turn-Taking Of Interrogation Recorded By Net’s 86 - Rima Muryantina (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2016)
Abstrak - The research focuses on exploring the power relations that occur in the recording of interrogation between a policeman, two pickpocket suspects, and the victim (who was also the witness) publicized by NET Mediatama Indonesia via its tv program: 86. The approach used to analyze the interrogation is the Conversation Analysis. Via Conversation Analysis, the researcher tries to reveal the structure of turn-taking in the interrogation and how this structure represents the power relations between the participants of conversation. The policeman, in this case, is presumed to be the man with higher power than the suspects and the victim, as he has the ability to control the behaviour of others while others cannot have such ability in the same area of behaviour (Meshtrie et. al 2009, p. 310). The analysis is then specified into determining the types of turn allocation: that current speaker selects the next speaker or that the next speaker selects himself (Liddicoat 2007, p. 63-67). The result of the analysis reveals that the patterns of turn allocation of the policeman are all self-selected. Meanwhile, the patterns of turn allocation of the suspects are mostly selected by the policeman as the current speakers. There are also some parts when the suspects self-select to take turn of talking when they feel like the accusation is not true and needs to be corrected. In addition, the patterns of turn allocation of the victim are mostly selected by the policeman, except in the part where he expresses dispreferences towards the suspects’ talk. In this part of the talk, the turn is self-selected. Aside from that, the analysis is also supported by the evidence of overlaps occuring in the conversation, where they occur the most when the suspects try to defend themselves but are denied by both the policeman and the victim. The problematic overlap is then resolved by the suspects, as the side of weaker power to discontinue the talk. The interesting finding of the analysis is that the victim has higher power than the suspects in the interrogation, as the man with the highest power (the policeman) takes sides on him. Keywords - Conversation Analysis, Language and Power, Language and Legal Process